Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.92910.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.929